IMPLEMENTASI PENYALURAN KUT DAN DAMPAKNYA TERHADAP PERKEMBANGAN KOPERASI UNIT DESA (KASUS KUD SETIA TANI DESA MAKMUR SEJAHTERA KECAMATAN GUNUNG SAHILAN) - Dwi Indrayani; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted in KUD Tani Makmur Sejahtera Faithful Districtof Mount Sahilan. The purpose of this research is to know and analyze theimplementation of the distribution of KUT in KUD Tani Faithful and to determine theimpact of the development of farmer cooperatives Faithful.For a sample taken from a population of 91 people or as many as 1020 thenumber of members of the cooperative. Data required in the writing of this manuscriptobtained by distributing questionnaires to the respondents who use the services of thecredit cooperatives and Bukopin using simple random sampling method is samplingof all members of the population was randomly without regard to existing strata in thepopulation members.Data analysis technique that I use in this paper is a descriptive statisticalanalysis techniques. Where once the data is collected, the data can be classifiedaccording to the indicators used in this study was then made a frequency table andthen interpreted. While the discussion is followed by the descriptions to better clarify.From the research that has been done, it is known that the implementation ofKUT and distribution and its impact on the development of the Faithful Farmercooperatives in collaboration with the overall Bukopin already categorized " GOOD "and are in accordance with prescribed standards. This is visible from most of thedebtor meets the criteria of the implementation of the loan portfolio.Keywords : Implementation and distribution of credit